2021
DOI: 10.1136/bmjopen-2020-047059
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology, course and treatment of acute tubulointerstitial nephritis in paediatric patients: a cross-sectional web-based survey

Abstract: BackgroundAcute tubulointerstitial nephritis (TIN) is a significant cause of acute renal failure in paediatric and adult patients. There are no large paediatric series focusing on the aetiology, treatment and courses of acute TIN.Patients, design and settingWe collected retrospective clinical data from paediatric patients with acute biopsy-proven TIN by means of an online survey. Members of four professional societies were invited to participate.ResultsThirty-nine physicians from 18 countries responded. 171 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…A repeated-biopsy study found that steroid treatment reversed active lesions and prevented chronic lesion progression [21]. Consequently, early steroid therapy in children may reasonably treat acute lesions before chronic ones develop [10, 22]. We initially treated our case with adequate doses of prednisone and lisinopril.…”
Section: Discussionmentioning
confidence: 99%
“…A repeated-biopsy study found that steroid treatment reversed active lesions and prevented chronic lesion progression [21]. Consequently, early steroid therapy in children may reasonably treat acute lesions before chronic ones develop [10, 22]. We initially treated our case with adequate doses of prednisone and lisinopril.…”
Section: Discussionmentioning
confidence: 99%
“…Main clinical and laboratory features of TINU include sudden onset of bilateral non-granulomatous anterior uveitis (rare posterior uveitis or panuveitis) associated with typical anterior uveitis symptoms (eye pain, redness, decreased vision, and photophobia) and mildly to moderately abnormal renal function, in particular elevated Creatinine with or without raised urea, high inflammatory markers (ESR, CRP), abnormal urinalysis (low-grade proteinuria, normoglycemic glucosuria, microscopic haematuria and elevated β2-microglobulin). To confirm the renal involvement, kidney biopsy can be considered demonstrating tubulointerstitial inflammatory infiltrations containing lymphocytes and non-specific histiocytes with vessels and glomeruli being typically spared ( 87 , 90 , 92 ). Apart from the mentioned above clinical and laboratory changes, most of the patients with TINU have systemic features, including fever, weight loss, fatigue, and abdominal/flank pain.…”
Section: Non-infectious Uveitismentioning
confidence: 99%
“…TINU is a rare benign autoimmune condition of unknown etiology characterized by combined ocular and renal damage. Usually, the eye inflammation precedes or is diagnosed soon after the accidental finding of renal abnormalities and associated systemic features (87)(88)(89).…”
Section: Tubulointerstitial Nephritis and Uveitismentioning
confidence: 99%
“…It is usually detected in teenagers with a median age of 13 years with a female preponderance [ 2 , 4 ]. Presenting features are often non-specific with initial reports of fatigue, nausea, vomiting, weight loss, myalgia, fever and often delayed onset eye symptoms of pain, erythema, photophobia and reduced visual acuity [ 5 ]. Alongside impairment of kidney function, patients can develop normo- or hypokalaemia with anaemia, eosinophilia and high erythrocyte sedimentation rate (ESR).…”
Section: Introductionmentioning
confidence: 99%